Parameterization of the coupling between strain and order parameter for LuF[SeO3]. (1st April 2014) - Magdysyuk, Oxana V.; Müller, Melanie; Dinnebier, Robert E.; Lipp, Christian; Schleid, Thomas
<x xml:space="preserve">Abstract</x> The high‐temperature phase transition of LuF[SeO3] has been characterized by time‐resolved high‐resolution synchrotron powder diffraction. On heating, a second‐order structural phase transition was found at 393 K, while on cooling the same phase transition occurs at 371 K, showing a large hysteresis typical for a first‐order phase transition. Detailed analysis using sequential and parametric whole powder pattern fitting revealed that the coupling between the strain and the displacive order parameter determines the behaviour of the material during the phase transition. Different possible coupling mechanisms have been evaluated and the most probable rationalized.